IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN JALAN BERKESELAMATAN DI DINAS PEKERJAAN UMUM BINA MARGA PROVINSI JAWA TIMUR - Bethari Ulfa Suryani (Faculty of Social and Political Science, 2016)
The high number of traffic accidents on the road caused by the low quality of the roads we need an regulations governing road safety, in particular the rules to minimize accidents caused by the quality of roads that do not fit the standard. importance of road safety regulation jatim due according to the data, the number of accidents in java is very high, even increasing. with the passing of The East Java provincial regulation no. 1 year 2014 on the implementation of road safety, with the purpose of (1) the establishment of roads that meet the standards roadworthy in accordance with the legislation in force; and (2) the realization of the road safety services that are safe, comfortable, orderly and smooth to drive the regional economy of East Java. This study aims to determine how the implementation of the policy of east java provincial regulation no. 1 of 2014 on the implementation of road safety and how obstacles in the implementation of these policies. The research used descriptive qualitative methods with observations, deep interview and documentation in collecting datas. results of research on implementation of east java provincial regulation no. 1 year 2014 on the implementation of road safety is DPU Bina Marga East Java Province, has implemented a policy of East Java Provincial Regulation 1 of 2014 on the implementation of road safety, it is reflected through a reduction in the number of accidents along jl. mastrip surabaya. obstacles that must be faced by the dpu bina marga in realizing the implementation of the road safety is in terms of finance, infrastructure, and the attitude of people who are less active in terms of complaints to the dpu bina marga east java province.